Resolution of C1q deposition but not of the clinical nephrotic syndrome after immunomodulating therapy in focal sclerosis - Tibor Tibor Fülöp; Éva Csongrádi; Anna A. Lerant; Matthew Lewin; Jack R. Lewin (Society of Diabetic Nephropathy Prevention, 2015)
Background: The natural evolution of C1q nephropathy (C1qNP) during immunosuppressive treatment is relatively little studied or understood. Case Presentation: A 30 year-old Caucasian female was referred to us for further management of biopsy-proven C1qNP and severe nephrotic syndrome. Serologic work-up remained negative, including complement C3 and C4 levels and repeated testing for antinuclear antibodies. A renal biopsy revealed minimal change nephropathy vs. focal sclerosis on light microscopy and C1qNP on immunopathology. She has failed trials of high-dose oral prednisone, mycophenolate mofetil 1,500 mg twice a day and a subsequent regimen of monthly IV cyclophosphamide 750 mg × 9 cycles. She also received the maximum tolerated angiotensin-converting enzyme inhibitor and spironolactone therapy. Random urine protein-to-creatinine (UPC) ratio predicted proteinuria in the range between 5-35 gm/day, while serum creatinine rose progressively from 1.0 mg/dL to 1.4 mg/dL (to convert to μmol/L, multiply by 88.4). A decision was made to repeat renal biopsy to reassess the underlying histology. The biopsy revealed focal sclerosis but no C1q deposition. Conclusions: Our case illustrates at least two points: first, an established pathologic diagnosis does not obviate the need for repeated renal biopsy later on, should diagnostic uncertainty persist. Second, histological diagnoses may evolve over time, especially in a patient receiving active and powerful immune-modulating treatment. In our case, the clinical nephrosis did not change with immunosuppressive therapy while C1q deposition ceased, making this latter entity likely the immunologically mediated process.